SPLEENIC ABSCESS AS A COMPLICATION OF EXTRAPULMONAY TUBERCULOSIS - Hashmi, Junaid Zia; Hashmi, Arifa Zia; Anwar, Shaheer; Ghafoor, Ammarah; Haider, Zeeshan; Zaheer, Faisal (Journal of Ayub Medical College Abbottabad, 2019)
Tuberculosis continues to be a fatal infectious disease in developing countries. Despite the advances in medical sciences and introduction of potent therapeutic regimes tuberculosis has still managed to survive and prevail worldwide. It can affect many organs of body. Isolated splenic tuberculosis is uncommon in immunocompetent host and only some cases are reported internationally. Extrapulmonary tuberculosis with splenic involvement is also rare and only comes after lungs and liver. We present a case of patient presented with complaints of prolonged fever, cough and insidious onset of abdominal pain and sepsis. Exploratory laparotomy revealed spleenic abscess as incidental finding associated with tuberculous perforation of colon. She underwent double barrel colostomy and spleenectomy followed by intensive care unit admission. Measures such as awareness about the disease, early medical assistance and good compliance regarding treatment can produce positive results in combating tuberculosis and its complications. Keywords: Extrapulmonary tuberculosis; Exploratory laprotomy; Spleenectomy